Inovasi Kurikulum Pendidikan SMA Darul Ulum 2 di Pondok Pesantren Darul Ulum Jombang: indonesia - MUHAMMAD NUR HAKIM; Mohammad Tholhah Hasan (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2019)
ABSTRACTIn this era of globalization the government has focused on pesantren to advance the quality ofeducation in Indonesia. The development of pesantren education must be carried out competitively. Pesantreneducation must also be able to provide a guarantee of the superiority of competent outputs. The developmentcarried out by Islamic boarding schools is an effort to produce superior outputs and outflows.This study aims to determine the innovations created by pesantren through schools by referring to thefollowing formulation: 1) school curriculum innovation. 2) the implications of school curriculum innovations onboarding schools, and 3) the relevance of school curriculum innovations to boarding schools.The results of the study show that: First, the curriculum innovation process is carried out through fivestages, namely 1) the formulation stage by introducing the pesantren education model, 2) the stage ofadjustment, the Cambridge curriculum is adjusted to the existing system, 3) the determination stage byestablishing an international curriculum adoption , 4) the stage of support, namely taking action to supportinnovation, 5) the stage of correction, which is a form of correction of the program implemented. Second, theimplications of the educational curriculum innovation in the school on the pesantren curriculum are found in thecurriculum component which includes: 1) curriculum content; 2) learning media; 3) learning strategies andlearning processes; and 4) evaluation; Third, school curriculum innovation is closely related, relevant, suitableand connected with the pesantren curriculum in the form of both the school curriculum and the boardingcurriculum.Keyword: Innovation, Curriculum, School, Boarding School.ABSTRAKDi era globalisasi ini, pemerintah telah fokus pada pesantren untuk memajukan kualitas pendidikan diIndonesia. Pengembangan pendidikan pesantren harus dilakukan secara kompetitif. Pendidikan pesantren jugaharus mampu memberikan jaminan keunggulan out put yang yang mampu bersaing. Pengembangan yangdilakukan oleh pesantren merupakan usaha untuk menghasilkan out put dan out come unggulan.Penelitian ini bertujuan untuk mengetahui inovasi yang diciptakan pesantren melalui sekolah denganmengacu pada rumusan berikut: 1) inovasi kurikulum sekolah. 2) implikasi inovasi kurikulum sekolah terhadappesantren, dan 3) relevansi inovasi kurikulum sekolah terhadap pesantren.Hasil penelitian menunjukkan bahwa: Pertama, proses inovasi kurikulum dilakukan melalui limatahap, yaitu 1) tahap perumusan dengan mengenalkan model pendidikan pesantren, 2) tahap penyesuaian yaitukurikulum cambridge disesuaikan dengan sistem yang ada, 3) tahap penetapan dengan melakukan penetapanterhadap adopsi kurikulum internasional, 4) tahap dukungan yaitu melakukan tindakan dukungan terhadapinovasi, 5) tahap koreksi, yaitu bentuk koreksi atas program yang dilaksanakan. Kedua, implikasi inovasikurikulum pendidikan di sekolah terhadap kurikulum pesantren terdapat pada komponen kurikulum yangmeliputi: 1) isi kurikulum; 2) media pembelajaran; 3) strategi pembelajaran dan proses pembelajaran; dan 4)evaluasi; Ketiga, inovasi kurikulum sekolah berkaitan erat, relevan, cocok dan nyambung dengan kurikulumpesantren baik berbentuk kurikulum sekolah maupun kurikulum asrama.Kata Kunci: Inovasi, Kurikulum, Sekolah, Pesantren.